Scanning Electron Microscopy of Invasion of Apple Leaves and Blossoms by Pseudomonas syringae pv. syringae - Mansvelt, E. Lucienne (1989)
Scanning electron microscopy indicated that Pseudomonas syringae pv. syringae L795 entered leaves through stomata and multiplied in the substomatal chambers. Strain L195 applied to blossoms colonized stigmas and also occurred in intercellular spaces of styles. Nonpathogenic strain L796 failed to colonize blossoms. This study suggests that inoculum of pathogenic P. syringae pv. syringae builds up on apple leaves and blossoms.